DAMPAK DIGITALISASI KURIKULUM EKONOMI SYARIAH TERHADAP KESIAPAN KERJA LULUSAN PERGURUAN TINGGI - Muhammad Fachry Syahputra; Aulia Rahmawati Harahap (Yayasan An-Nur Meunara Baro, 2026)
The digital competency gap between university graduates and the needs of the Islamic finance industry 4.0 is a serious barrier to labor absorption. To measure the impact of Islamic economics curriculum digitalization on graduate work readiness, specifically in the Islamic Finance Industry and Digital Hub area of Medan Petisah. This study uses a descriptive quantitative approach through surveys of alumni and final-year students, as well as interviews with industry practitioners. Analysis was conducted on technology literacy and work adaptability variables. The results show that the integration of financial technology in the syllabus, such as the use of computerized sharia banking laboratories and understanding smart contracts, significantly increases graduate competitiveness. Industry-based internships (MBKM) are also proven to strengthen students' professional mentality. However, infrastructure constraints and the readiness of faculty members remain institutional challenges that need to be addressed. Curriculum digitalization is no longer an option but a necessity to produce Muslim technocrats capable of operating digital sharia financial systems competently and with integrity.